Ultrathin broadband metasurface-based absorber comprised of tungsten nanowires - R.M.H. Bilal; M.A. Baqir; P.K. Choudhury; M.A. Naveed; M.M. Ali; A.A. Rahim (Results in Physics, 2020)
An ultrathin broadband metasurface-based absorber, comprised of tungsten nanowires, was studied under the normal and oblique incidence of transverse electric (TE) and transverse magnetic (TM) waves. The effect of geometrical parameters on the absorption spectra was investigated through the surface electric field and power patterns at certain operating wavelengths. The structure was found to exhibit nearly perfect absorption in the ultraviolet (UV) span of ~350–400 nm and ~85% absorptivity in the visible spectral range of ~400–750 nm. The attempt was also made to validate the simulation results with that obtained upon homogenization of the metasurface using the effective medium theory. Further, to optimize the results, the performance of the proposed absorber was analyzed in terms of the figure of merit and operating bandwidth, the highest values of which were obtained to be 95% and 450 nm, respectively. With the viewpoint of achieving relatively wideband absorption, it is expected that the proposed absorber can be effectively used in biosensing, solar cell and thermal emitter applications.